2018
DOI: 10.1002/oby.22113
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulatory Mechanisms in Adipose and Muscle Tissue Associated with Composite Glucometabolic Phenotypes

Abstract: ObjectiveTissue-specific gene expression is associated with individual metabolic measures. However, these measures may not reflect the true but latent underlying biological phenotype. This study reports gene expression associations with multi-dimensional gluco-metabolic characterizations of obesity, glucose homeostasis, and lipid traits.MethodsFactor analysis was computed using orthogonal rotation to construct composite phenotypes (CPs) from 23 traits in 256 non-diabetic African Americans. Genome-wide transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Our previous transcriptome-wide association study (TWAS) analyses identified 7,464 glucometabolic trait-associated transcripts significantly associated with at least 1 of the 23 individual traits and six composite glucometabolic phenotypes tested at Benjamini-Hochberg false discovery rate (FDR)-corrected P value ,0.01 in AT of AAGMEx participants (5,6,28,33). The eQTM analysis used linear regression, as implemented in MatrixEQTL to test whether DNAm levels were associated with transcript expression levels of these glucometabolic trait-associated transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous transcriptome-wide association study (TWAS) analyses identified 7,464 glucometabolic trait-associated transcripts significantly associated with at least 1 of the 23 individual traits and six composite glucometabolic phenotypes tested at Benjamini-Hochberg false discovery rate (FDR)-corrected P value ,0.01 in AT of AAGMEx participants (5,6,28,33). The eQTM analysis used linear regression, as implemented in MatrixEQTL to test whether DNAm levels were associated with transcript expression levels of these glucometabolic trait-associated transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous AT biopsy samples collected from 230 individuals without diabetes from the AAGMEx cohort (5,6) were used for epigenome-wide DNAm profiling. The clinical and anthropometric characteristics of the AAGMEx cohort have been previously described (5,6,28). Briefly, cohort participants were healthy, self-reported AA men and women residing in North Carolina, aged 18-60 years, with a BMI between 18 and 42 kg/m 2 (Supplementary Table 1).…”
Section: Human Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have for the first time systematically catalogued eQTL in equine skeletal muscle, both at rest and post-exercise. Previous investigations of eQTL in skeletal muscle have focussed primarily on human T2D (Sharma et al, 2011; Keildson et al, 2014a; Sajuthi et al, 2016; Langefeld et al, 2018) and meat quality traits in production animals (Ponsuksili et al, 2015; Gonzalez-Prendes et al, 2017; Pampouille et al, 2018; Gonzalez-Prendes et al, 2019; Velez-Irizarry et al, 2019). Our investigation of eQTL in the context of skeletal muscle and exercise present some of the only work to-date in this area (Kelly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We have for the first time systematically catalogued eQTL in equine skeletal muscle, both at rest and post-exercise. Previous investigations of eQTL in skeletal muscle have focussed primarily on human T2D (Sharma et al, 2011; Keildson et al, 2014a; Sajuthi et al, 2016a; Langefeld et al, 2018)and meat quality traits in production animals (Ponsuksili et al, 2015; Gonzalez-Prendes et al, 2017; Pampouille et al, 2018; Gonzalez-Prendes et al, 2019; Velez-Irizarry et al, 2019). Our investigation of eQTL in the context of skeletal muscle and exercise present some of the only work to-date in this area (Kelly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%